Pengaruh Lingkungan Bisnis terhadap Informasi Akuntansi Manajemen dan Penganggaran Dampaknya terhadap Kinerja Perusahaan - Astuty, Widia (Jurnal Trikonomika, 2012)
This study aims to find empirical evidence on the effect of the managerâs perception about the business environment on the characteristics of management accounting information; find empirical evidence on the effect of the managerâs perception about the business environment on the characteristics of budgeting; and find empirical evidence on the effect of the managerâs perception of the environment bisnisl, characteristics of management accounting information, budgeting and the performance characteristics of a manufacturing company in Medan Industrial Estate. The method used is descriptive survey method and explanatory survey method. The data used are the primary data using a questionnaire addressed to the marketing and production manager and president of the company with a Likertâs scale. This study uses census of the entire population as the unit of analysis as much as 103 manufacturing companies in Medan Industrial Estate. Data analysis was used path analysis. The results showed that a) the perception of managers of the business environment affect the characteristics of management accounting information; b) perceptions of managers about the business environment affect the characteristics of budgeting; and c) perceptions of managers about the business environment, characteristics of management accounting information, and budgetary characteristics affect the performance of the company.